Development Of Transversal Skills In Content And Language Integrated Learning Classes - Macianskiene, Nemira (European Scientific Journal, ESJ, 2016)
The issue of transversal or soft skill development is an important challenge for educational institutions preparing prospective employees for successful integration in the modern global labour market. The implementation of content and language integrated learning (CLIL) provides ample opportunities for the development of soft skills, apart from in-depth learning of the subject and development of language competences. The study presents some insights gained during the in-service training courses for secondary school teachers, while implementing the European Social Fund supported project “Synergy of Content and Foreign Language” at the Institute of Foreign Languages of Vytautas Magnus University in Lithuania, with regard to possibilities to better prepare graduates for social integration through efficient implementation of CLIL at school. Among other objectives, the project aimed at professional development of secondary school subject teachers by raising their awareness of CLIL methodology, including transversal skill development. The paper presents investigation into teacher perception of the importance of soft skills and their self-evaluation of practice of soft skill integration into their subject teaching. The issue of transversal skill development is discussed as an integral constituent of project activities, an added value and/or the synergic effect which may be achieved while implementing CLIL at school. The study concludes that CLIL implementation requires the whole school policy, new approach to subject and language teacher in-service training and presents some recommendations for educational policy developers.